Drinking water preference among students in UiTM Perlis using fuzzy AHP / Nur Fatihah Fauzi, Syahirah Ali Munawar, and Huda Zuhrah Ab Halim - Fauzi, Nur Fatihah; Ali Munawar, Syahirah; Ab Halim, Huda Zuhrah (UiTM Cawangan Perlis, 2020)
Due to the decrease in groundwater quality, as a result for Malaysia's to make the bottled water as their basic source of drinking water. It is a fact that each bottled water contains various types of minerals and each mineral will have its own benefits for general human health. Calcium, magnesium, zinc, iron, sodium, and more are common kinds of minerals found in bottled water. The type of minerals that are in the bottled drinking water depends on the water source. Many customers around the world, particularly Malaysians, have turned to bottled water as their primary source of potable water. The research was performed to determine the best and most preferred brands of mineral bottled water available in UiTM Arau, Perlis in terms of its advantages and everyday mineral content. Fuzzy AHP is a hybrid method that combines Fuzzy Set Theory and AHP. It has been developed to take into account uncertainty and imprecision in the evaluations. The decision-making method used by multi-criteria is the FAHP method as an approach to the problem of selection bottled with mineral water. In this paper, the mineral water brands bottled namely "Spritzer," "Bleu" and "Ice Mountain" are analyzed and presented as sold in UiTM Perlis. The criterion given is price, availability, taste, water source, and packaging. Comparison is made between these three brands to decide which of these brands is more favoured and desirable among UiTM Perlis students based on the weight of alternatives regarding the criteria. The results obtained were that Spritzer has the greatest total score with a weight of 0.439. The analysis shows that the "Spritzer" brand is better compared to the other two daily life consumption brands, which weight is 0.439 with 5 criteria. Bleu, however, offers a better weighty flavour, 0.386 of those two brands of mineral water bottles. This study can be a factor in influencing consumer behaviour and providing information to local bottled water companies' marketers. It will ultimately increase their profitability and revenue by new and better marketing techniques. In addition, bottled water producers can also produce bottled water that meets the needs of Malaysian consumers. In addition, this study will provide consumers with a greater understanding of the standard of bottled water that may affect the environment, such as pollution, etc. This study will also benefit both marketers and consumers by helping them make educated decisions on choosing the most appropriate mineral water bottled for consumption in keeping with their health concerns these days.